A review of new media in Malaysia: issues affecting society - Alivi, Mumtaz Aini; Ahmad Ghazali, Akmar Hayati; Tamam, Ezhar; Osman, Mohd Nizam (Human Resource Management Academic Research Society, 2018)
Growth of new media plays a great role in society and political landscape in Malaysia. Thus, it is imperative to understand the main issues arising from development of new media, which affects the society. This paper therefore aims to explain how issues pertaining to new media has affected Malaysia. Three key issues will be discussed, namely, credibility, influence in the political landscape, and effectiveness in providing information to the public. Review of past literature and studies showed that credibility of online news is crucial whereby demand for reliable information is rising to compete with traditional media, which has been proven to be a credible source many decades ago. Moreover, in recent years, new media through online news has been influencing the political discourse in Malaysia with the help of many interesting features offered by that medium.